TRAVEL TIME VARIABILITY OF TRANS METRO BANDUNG BUS CORRIDOR II - Ramadhan, Hafiz Janitra; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Travel time variation indicates the reliability of bus operating systems and affects passenger satisfaction. This study aims to calculate and compare travel time variability of Trans Metro Bandung Bus Corridor II Route Cicaheum-Cibeureum among days. The analysis shows that the system has travel time variability range from 0,0007% up to 15,5%. This is caused by route changes and the effects of congestion. The comparison of travel time variability among days shows that the value of travel time is more stable in weekend than weekday.